Nanomaterials: from research to applications - Hosono, H (Elsevier, 2006)
Function cultivation in transparent oxides utilizing natural and artificial nanostructures / H. Hosono and M. Hirano; The role of lattice defects in oxides / M. Itoh ; Size effect of ferroelectric and high permittivity thin films / H. Funakubo ; Photonic devices using liquid crystal nanostructures / H. Takezoe ; Nanocylinder array structures in block copolymer thin films / K. Kamata, T. Iyoda ; Nano-size charge inhomogeneity in organic materials / T. Mori ; Size control of nanostructures by quantum confinement / H. Hirayama ; Grain boundary dynamics in ceramics superplasticity / F. Wakai, A. DomiÌnguez-RodriÌguez ; Nanostructure control for high-strength and high-ductility aluminum alloys / T. Sato ; Nanoporous materials from mineral and organic templates / K. Okada, K.J.D. MacKenzie ; Enhancement of thermoelectric figure of merit through nanostructural control on intermetallic semiconductors toward high temperature applications / Y. Mishima, Y. Kimura, S. Wng Kim ; Smart coatings : multilayered and multifunctional in-situ ultrahigh-temperature coatings / H. Hosoda.